CHALLENGES IN IMPLEMENTING GOVERNANCE POLICIES FOR THE PROTECTION OF INDONESIAN MIGRANT WORKERS - Wajid Fauzi,; Roy Valiant Solomon,; Eko Prasojo, (International Journal of Innovative Technologies in Social Science, 2023)
The Indonesian Migrant Workers Protection Governance Policy, outlined in Law No. 18/2017, has faced challenges in effectively protecting migrant workers. Despite being in effect for over three years, issues such as black markets and brokering practices persist, and institutional problems hinder policy implementation. This study examines the factors that influence policy implementation by analyzing relevant government and non-government institutions. Utilizing Mazmanian and Sabatier's theory (1983) and Grindle's theory (1980), the research identifies problem characteristics, policy characteristics, and policy environment as key factors. Bovaird and Loefler's (2016) Governance concept is also used to formulate directions for implementation improvement. The study finds that while some elements, such as the exemption of placement fees, establishment of Integrated Services, and provision of social security, have been implemented, other critical elements like the role of regions in preparing funds and training have not been implemented. Additionally, the research identifies diverse prospective Indonesian Migran Worker (PMI) behavior, hierarchical integration between institutions, and socio-economic conditions during the Covid-19 pandemic as the main factors affecting policy implementation. To improve policy implementation, the study suggests four interventions, including high-level leadership coordination, completion of implementing rules, policy socialization and supervision, and enforcement of legal rules.